Alternative assets – a new challenge to property? An analysis of superannuation funds. (3rd May 2016) - Reddy, Wejendra
Abstract: Leading Australian superannuation funds now have major exposure of approximately 20% to a sector classified as alternative assets. Within this sector, there are infrastructure products, which have similar characteristics to property. Thus, an ongoing debate on whether alternatives can replicate the performance of property in mixed-asset portfolios. This research examines the diversification benefits of property, infrastructure, private equity, hedge funds and commodities within two-asset and multi-asset optimisation portfolios. It uses ex-post data (1995–2015), from A431 billion industry superannuation funds balanced portfolio. The methodology also involves substituting smoothed with desmoothed property data to detect any subsequent change in property allocation levels. The results from the two-asset portfolios illustrate that including infrastructure, hedge funds and private equity in the direct property portfolio provides high risk-adjusted returns (.45–.51), although portfolio weight is dominated by direct property. Analysis on multi-asset portfolios clearly shows that substituting smoothed property with desmoothed property data is insignificant to both industry fund performance and its weighting to property. Despite similar asset allocation range assigned to property and infrastructure (0–20%), infrastructure allocation was 3%, lower than property (13%). Strong allocations to property highlight its significance in institutional portfolios, even with the availability of similar alternative assets. For industry superannuation funds, the empirical results show that allocation to property can be higher than current 10%, backed by improved portfolio risk-adjusted returns. The research contributes to both practical and academic fields as it offers a methodological approach on how allocation to property assets can be improved using a series of asset allocation strategies.